Tinjauan “Novum” Dalam Peninjauan Kembali Sengketa Tata Usaha Negara - Setyono, Yoni A. (Jurnal Hukum & Pembangunan, 2019)
Novum is one of the reasons for conducting a review. Sometimes in one case, there is an intersection between two courts. In writing, it tries to examine the intersection between Novum in civil cases and cases of state administrative disputes. Which more relevant link point is used regarding the period of time in filing EIA problems in state administrative disputes. Subject to the legal requirements of civil cases (Environmental Law) or in the Administrative Procedure Law. This study begins with a comparison of approaches through proof known in civil cases and in state administrative disputes which are finally sent to the mechanism of submitting the novun This writing is intended to have legal certainty in submitting novum if there are two links.